The spiritual vernacular of the early Ottoman frontier : the Yazcoglu family - Grenier, Carlos (Edinburgh Studies on the Ottoman Empire, 2021)
This study follows the lives and ideas of the Yazıcıoğlu brothers Mehmed Yazıcıoğlu and Ahmed Bican, Sufis of the frontier city of Gelibolu and authors of the most popular religious writings in Ottoman Turkish.